Liberdade e vinculação na fenomenologia hermenêutica - Lopes, Marcelo Vieira (2017)
Heidegger, since the late 1920’s, develops an extensive approach on human existence in terms of comprehension of being. Such approach is linked to the famous recovery of the problem of being, which will be, definitely, a main problem during all his work. The question on the meaning of being as the main reason of Heidegger’s philosophy arises, in the period of Being and Time, as inherently connected to the problem of a comprehension that is historically set. The human being, thus, to comprehend something like this, implies an articulation of the comprehension in different regulatory ways, in which the entities show up on the inside of a meaning field. The hermeneutic phenomenology of Being and Time might be understood, then, as the thematization of the articulation of the meaning throughout the normativity inherent to the entities which express. In this context arises the development of the freedom concept. Notwithstanding the plural-significance of this concept in Heidegger’s work, it is possible to find a subjacent sense in its appearances by the late 1920’s until 1930’s. That sense points out to a previous binding, as a possibility of the whole comprehension of being. Taken by the notion of binding, the concept of freedom points out to the immediate dissociation of its traditional notion. This work analyses the development of this concept in the aforementioned period, bearing in mind its acknowledged importance performed in the description of human existence in terms of comprehension of being.